ANALYSIS OF ARABICA COFFEE (Coffea arabica) GROWTH UNDER THE SUREN (Toona sureni) SHADE TREE IN GENTENG VILLAGE, SUKASARI DISTRICT, SUMEDANG REGENCY - Darliana, Ina; Ryadi, Giga; Wahyuni, Dwi; Meyranti, Risky; Rombeallo, Esra; Hapsari, Saprilian Stya (Universitas Veteran Bangun Nusantara, 2025)
Arabica coffee (Coffea arabica) is one of the leading plantation commodities whose growth is strongly influenced by environmental conditions, particularly the availability of shade from canopy trees. This study was conducted to analyze the influence of suren trees (Toona sureni) on the growth of Arabica coffee of the Ateng Super variety in Genteng Village, Sukasari District, Sumedang Regency. The research was carried out in April–May 2025 on a 0.7 ha community owned land with a sampling intensity of 15%. The observed parameters included total height, clear bole height, and diameter of suren shade trees, as well as the number and length of productive branches of coffee plants. Data were analyzed using classical assumption tests and multiple regression with t-tests through RStudio software.The results showed that the morphological characteristics of suren trees total height, clear bole height, and diameter did not directly influence the number or length of productive branches of Arabica coffee. Nevertheless, the presence of suren as a shade tree played an important role in creating a microclimate conducive to coffee growth. Microclimate observations indicated that suren shade could maintain ideal temperature and humidity ranges, namely 22–24°C and 72–83%, thereby helping stabilize the growing environment for coffee plants. With these capabilities, suren trees are considered suitable as shade species in Arabica coffee agroforestry systems. Their presence does not hinder coffee plant growth; instead, they contribute to establishing optimal environmental conditions for vegetative development and overall plant productivity. Keywords: Agroforestry, Coffea arabica, Shade tree, Rstudio, Suren